Pengaruh Putusan Mahkamah Konstitusi Nomor 18/Puu/Xvii/2019 Terhadap Eksekusi Jaminan Fidusia (Studi Pada Pt. Adira Dinamika Multifinance Tbk Cabang Bengkulu) - Meliza, Meliza (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
Currently, the need for cars or motorbikes is no longer dominated by people with strong economies. Small and medium businesses are also starting to use these two types of vehicles in developing their business and productivity so that car/motorbike rentals continue to increase. The purpose of this research is to find out and analyze the implementation system of fiduciary guarantees at PT. Adira Dinamika Multifinance, Tbk Bengkulu Branch. (ADMF), especially after the Constitutional Court decision no. 18/PUU/XVII/2019. Empirical legal research is the method used, and the format or presentation of research findings about the laws that apply in society. The central point of the research is not on the theory and formulation of norms but on how the law works in PT. ADMF. The results of the study are the application of fiduciary guarantees made to customers who default by taking back collateral from their own or third parties who receive facilities. Involve the recipient of the facility to show where the collateral is sold or transferred in order to return the collateral, which has not been completed and has not been resolved, it will be resolved in the fairest way possible. According to the Ruling of the Constitutional Court Number 18/PUU-XVII/2019, namely "the execution of a fiduciary guarantee cannot be carried out unilaterally by the creditor and must go through a District Court decision unless there is an agreement between the debtor and the creditor to resolve this execution issue.